CO2 activation by permethylpentalene amido zirconium complexes. Issue 13 (29th March 2021) - Hamilton, Elizabeth A.; Kilpatrick, Alexander F. R.; Turner, Zoë R.; Fraser, Duncan A. X.; Buffet, Jean-Charles; O'Hare, Dermot
Abstract : Synthesis and characterisation of new permethylpentalene (Pn*) zirconium bis(amido) and Pn*Zr cyclopentadienyl mono(amido) complexes and their reactivity with carbon dioxide. Abstract : We report the synthesis and characterisation of new permethylpentalene zirconium bis(amido) and permethylpentalene zirconium cyclopentadienyl mono(amido) complexes, and their reactivity with carbon dioxide.